Implementasi Sistem Cash On Delivery (COD) Cek Dulu dalam Memberikan Keamanan, Perlindungan Konsumen dalam Transaksi di Platform E-Commerce Shopee di Indonesia - Ketut Yuli Widiasari (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
In ever-evolving era of e-commerce, the Cash on Delivery (COD) Check First feature implemented by Shopee provides a practical solution for consumers who want to ensure security while shopping online. This feature allows buyers to inspect the condition of the product directly before deciding to make a payment. With this feature, consumers can verify that the item received matches the description listed on the platform, thus reducing the risk of fraud or product discrepancies. The transaction security offered through this system is one of the key aspects in increasing consumer trust in e-commerce platforms. This research aims to examine how the COD Check First feature provides additional protection for consumers in e-commerce transactions, particularly concerning the potential risks of fraud or product discrepancies that are common in online trade. This feature gives buyers more control to ensure that the received goods meet their expectations and the product description. Therefore, COD Check First not only facilitates the transaction process but also strengthens consumer protection, making it a relevant mechanism to minimize buyer dissatisfaction in e-commerce, especially in Indonesia.